Antifungal mechanism of (E)-2-hexenal against Botrytis cinerea growth revealed by transcriptome analysis - Song, Ge; Du, Shenglong; Sun, Helong; Liang, Quanwu; Wang, Haihua; Yan, Mingli; Zhang, Jihong (Frontiers in Microbiology, 2022)
Grey mold caused by Botrytis cinerea, a necrotrophic plant pathogen, is the most damaging diseases of tomato both pre- and post- harvest losses. (E)-2-Hexenal dose-dependently inhibited the mycelial growth of Botrytis cinerea. (E)-2-Hexenal caused distortion of the mycelia and loss of cytoplasm content, thus altering the morphology of B. cinerea hyphae. To know the molecular processes in response to (E)-2-hexenal, transcriptome sequencing was carried out using RNA-Seq techology. RNA-Seq results revealed that a total number of 3893 differentially expressed genes (DEGs) were identified in (E)-2-hexenal-treated B. cinerea, of which 1949 were found to be up-regulated and 1944 were down-regulated. Moreover, 2113 unigenes were mapped to 259 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Moreover, (E)-2-Hexenal stress affected the expression of genes involved in the pathways of cell wall, cell membrane and energy metabolism. KEGG pathway analysis showed that the terpenoid backbone biosynthesis and steroid biosynthesis were the most enriched in ergosterol biosynthetic process transcriptome data. Particularly, (E)-2-hexenal fumigation had influenced ergosterol biosynthetic gene expression levels (e.g. ERG1, ERG3, ERG4, ERG7, ERG12, ERG13, ERG24, ERG25, ERG26, ERG27), which were in good agreement with the experimental measurement results, and the ergosterol content decreased. Collectively, the results of this study increase our current understanding of (E)-2-hexenal inhibition mechanisms in B. cinerea and provide relevant information in postharvest shelf life extension and preservation of fruits and vegetables.